1998
DOI: 10.1007/s001270050024
|View full text |Cite
|
Sign up to set email alerts
|

Psychological disturbance among 5- to 8-year-old school children: a study from India

Abstract: This paper presents findings on the prevalence of psychological disturbance among a sample of 5- to 8-year-old Indian school children. The study was cross-sectional with a two-instrument, two-phase design. In the first phase (screening), 48 teachers rated 1535 children (810 boys and 725 girls) drawn from five schools in Bangalore city on the 26-item Children's Behaviour Questionnaire (CBQ). This resulted in 281 children being identified as disturbed, giving a prevalence of 18.3%. In the second phase, 279 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…This was comparable to others studies done in India 5,6 Most commonest disorder in our study was conduct disorder 2.75% which replicates the results of study done by Ahmad et al from the same country. 7 Externalizing problems were the most common disorder in this study (9.75%) which goes along the finding of Shenoy et al 8 Girls (Age group of 13 to 15) had more of internalizing behavioral (3.5%) problems whereas boys (Age group of 5 to 12) had more of externalizing problems (7.5%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was comparable to others studies done in India 5,6 Most commonest disorder in our study was conduct disorder 2.75% which replicates the results of study done by Ahmad et al from the same country. 7 Externalizing problems were the most common disorder in this study (9.75%) which goes along the finding of Shenoy et al 8 Girls (Age group of 13 to 15) had more of internalizing behavioral (3.5%) problems whereas boys (Age group of 5 to 12) had more of externalizing problems (7.5%).…”
Section: Discussionsupporting
confidence: 89%
“…8,9 as already found by Srinath et al, the majority of children who had conduct disorder and ADHD were from the rural background. 5 Children who met the criteria for conduct disorder and ADHD were from lower socioeconomic status which is statistically significant.…”
Section: Discussionsupporting
confidence: 69%
“…In India, Bhargava [17] found a high prevalence of depression (10%) in children. Shenoy et al [18] reported lower rates of internalizing as compared to externalizing disorders in a survey of 5-to 8-year-old school children. Choudhury et al [19] studied reported prevalence of 0.98% unipolar depression among 813 child and adolescent cases in a tertiary care centre in Bangalore.…”
Section: Introductionmentioning
confidence: 99%
“…They found factors for failure given by students as 'poor quality of teaching and lack of previous preparation' and 'high cultural expectancy on the part of teachers, parents and administrators' as key reasons for their failures. There are very few Indian studies on the academic problems in school children (Shenoy, Kapur & Kaliaperumal 1998). Although not based on perceptions or attributions about reasons for academic problems, Shah (2007) interviewed high school students in Mumbai on their reactions to failure, and their view on parental aspirations, and whether the children perceived any stigma owing to academic failure.…”
Section: Introductionmentioning
confidence: 98%